1997
DOI: 10.1177/096228029700600405
|View full text |Cite
|
Sign up to set email alerts
|

Optimal statistical design for toxicokinetic studies

Abstract: Optimal statistical design strategies are applied to toxicokinetic experiments, for determining proper allocations of subjects and/or spacings of sampling times under a variety of nonlinear concentration-time models. The strategies include: (i) optimal allocations of subjects assuming the placement of time points is fixed, (ii) optimal spacing of design time points while assuming an equal allocation of subjects per time points and (iii) allocations/time-point spacings optimized jointly. Emphasis is placed on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Measurement errors on the experimental data, sparseness of those, and model simplifications or mispecifications are translated into uncertainties in the parameter values determined by statistical fitting to such data. Uncertainty may be reduced by further experiments, the design of which can be formally optimized (72,73), or by a better understanding of the actual processes under study.…”
Section: Calibration Uncertainty and Variabilitymentioning
confidence: 99%
“…Measurement errors on the experimental data, sparseness of those, and model simplifications or mispecifications are translated into uncertainties in the parameter values determined by statistical fitting to such data. Uncertainty may be reduced by further experiments, the design of which can be formally optimized (72,73), or by a better understanding of the actual processes under study.…”
Section: Calibration Uncertainty and Variabilitymentioning
confidence: 99%
“…Uncertainty may be reduced by new experiments, the design of which can be optimised to bring a maximum of information (Beatty and Piegorsch, 1997) , or by a better understanding of the biology and hence better models. This may take much efforts and decisions routinely need to be quickly made despite a fair amount of uncertainty about the situation examined.…”
Section: Introductionmentioning
confidence: 99%
“…That is, replicates of animals may be assigned at each time point, but sampled only once often after sacrificing them. A review methodology for study design in toxicokinetics/pharmacokinetics can be found in Beatty and Piegorsch (1997).…”
Section: Introductionmentioning
confidence: 99%